Psychological Capital and English as a Second Language Classroom Management in Malaysia: The Moderating Effect of Teaching Experience - Wu, Yong; The, Hery Tanto; Lai, Siow Li (Frontiers in Education, 2022)
This research explores the influence of the psychological capital of elementary ESL (English as a second language) teachers in Malaysia on their classroom management and the moderation effect of their working experience on the influential relationship between Psychological capital and ESL classroom management. A survey conducted with 675 Malaysian elementary teachers took part in this research, with 24 teachers identified by followed up interviewing. From quantitative and qualitative analyses, the results show that psychology capital of elementary ESL teachers has a significant positive influence on classroom management. Teaching experience demonstrates a significant moderation effect in the casual correlation of psychological capital to ESL classroom management. The influence of the psychological capital of novice teachers on their classroom management is better than experienced teachers. Some implications and limitations are put forward.